HUBUNGAN ANTARA KEHARMONISAN KELUARGA DENGAN SIKAP DISIPLIN SISWA - Ani Endriani (Universitas Pendidikan Mandalika, 2017)
The purpose of this study was to determine the relationship between family harmony and disciplinary attitude of grade VII students of SMP Negeri I Janapria. The population in this study were all class VII students of SMP Negeri I Janapria, totaling 174, while the sample used was 15% of the total population, namely 26 students, while the sampling technique used proportional random sampling technique. Data collection techniques used questionnaires, documentation, and data analysis techniques used product moment correlation. The results showed that there was a relationship between family harmony and disciplinary attitude of the VII grade students of SMP Negeri I Janapria which was obtained based on data analysis using the correlation formula, the results obtained were r count of 3.841, while the value of r table at the 5% significance level with N = 26 was obtained. amounting to 0.388. Thus, the calculated r value is greater than the r table value of 3.841> 0.388. The results of the research and data analysis indicate that the alternative hypothesis (Ha) which says